(untitled) (Biomedical Research and Therapy, 2021)
In most people, COVID-19 presents as a mild disease. However, in many people, especially those with comorbidities, profound inflammation manifesting as a cytokine storm may lead to acute respiratory distress syndrome and multi-organ failure. This novel study reports two severe COVID-19 patients from Koja Regional Hospital: a male aged 52 and a female aged 65. Both patients had poor prognoses based on prognostic biomarkers, disseminated intravascular coagulation, nosocomial infections, and were reintubated more than once. Both patients were treated with adjunct autologous activated platelet-rich plasma — a safe and promising therapy — and were ultimately discharged. Thus, this study reports the potential of autologous activated platelet-rich plasma as supportive therapy for severe COVID-19 patients.